The Integration Of The Transformation Of Surcharge In The MDR System: An Analysis Of Islamic Law And Educational Management In QRIS Services - Muhammad Rohmat Hidayat; Nur ‘Azah; Masrokhin; Vian Hanes Andresetya; Sirojuddin Abror (International Journal of Interdisciplinary Research, 2026)
This study examines the transformation of the surcharge scheme in the Merchant Discount Rate (MDR) system within the Quick Response Code Indonesian Standard (QRIS) from the perspectives of Islamic law and educational management. The rapid development of digital payment technology has shifted the burden of transaction costs, initially borne solely by merchants, to also include consumers. This shift raises questions of justice, transparency, and compliance with Islamic principles. Employing a qualitative descriptive approach through literature study, the research integrates normative-theological analysis with educational management perspectives. The findings reveal that, from an Islamic legal standpoint, surcharge practices are permissible as long as they are conducted transparently, based on mutual consent, and do not lead to injustice. From the perspective of educational management, this issue can be integrated into curricula as part of Islamic financial literacy and further developed through case-based learning methods. Therefore, the transformation of the MDR QRIS system not only affects the economic sphere but also has strategic implications for Islamic education management.